2022
DOI: 10.1038/s42003-022-04276-x
|View full text |Cite
|
Sign up to set email alerts
|

Semi-field and surveillance data define the natural diapause timeline for Culex pipiens across the United States

Abstract: Reproductive diapause serves as biological mechanism for many insects, including the mosquito Culex pipiens, to overwinter in temperate climates. While Cx. pipiens diapause has been well-studied in the laboratory, the timing and environmental signals that promote diapause under natural conditions are less understood. In this study, we examine laboratory, semi-field, and mosquito surveillance data to define the approximate timeline and seasonal conditions that contribute to Cx. pipiens diapause across the Unite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 85 publications
(150 reference statements)
1
9
0
Order By: Relevance
“…WNV exhibits clear seasonal transmission trends in Culex populations and human cases, with infections peaking in the late summer across the United States (5,6), yet the mechanisms driving these seasonal trends have been largely unexplored. Although previous studies have suggested that the spatiotemporal abundance of Culex vector populations in the summer and late summer can lead to increased levels of WNV infection in mosquito populations (14,52), overall Culex abundance in Iowa typically peaks much earlier in the season (i.e., May/June) (5,11,14,51,52). Therefore, combining both mosquito abundance and infection data (vector index) is more predictive than mosquito abundance alone in predicting human WNV cases (63-66), demonstrating the importance of identifying the physiological components that contribute to mosquito infection and transmission of WNV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WNV exhibits clear seasonal transmission trends in Culex populations and human cases, with infections peaking in the late summer across the United States (5,6), yet the mechanisms driving these seasonal trends have been largely unexplored. Although previous studies have suggested that the spatiotemporal abundance of Culex vector populations in the summer and late summer can lead to increased levels of WNV infection in mosquito populations (14,52), overall Culex abundance in Iowa typically peaks much earlier in the season (i.e., May/June) (5,11,14,51,52). Therefore, combining both mosquito abundance and infection data (vector index) is more predictive than mosquito abundance alone in predicting human WNV cases (63-66), demonstrating the importance of identifying the physiological components that contribute to mosquito infection and transmission of WNV.…”
Section: Discussionmentioning
confidence: 99%
“…Several mosquito-borne pathogens, such as malaria, dengue, and West Nile virus (WNV), display seasonal patterns in their transmission (1)(2)(3)(4)(5)(6) that are driven by environmental variables that influence mosquito life-history traits (7)(8)(9), physiology (10,11), and abundance (11)(12)(13)(14), which ultimately shape mosquito-borne disease transmission (15). However, there is little information on how seasonal trends may influence mosquito susceptibility to pathogen infection.…”
Section: Introductionmentioning
confidence: 99%
“…Semi-field studies have found that 50% of Cx. pipiens initiate diapause around mid-September in Ames, Iowa (latitude 32.0°N; [ 24 ]) and at higher latitudes, diapause initiation occurs earlier with 50% of the population entering diapause around mid-July in Guelph, Ontario, Canada (latitude 43.4°N; [ 25 ]). One field study in Boston, Massachusetts (latitude 42.4°N; [ 26 ]) found that adult Cx.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous semi-field studies have characterized how photoperiod and temperature induce diapause in larvae of Cx. pipiens [ 24 , 25 ] and another study characterized the diapause incidence of female Cx. pipiens collected in a single overwintering site from August to mid-November [ 26 ], our study is unique in that it determined how long non-diapausing and reproductively active mosquitoes persist in the field across multiple sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation